Situational action theory and school bullying: rethinking the moral filter - Liu, Weidi (Crime & delinquency, 2022)
Utilizing a sample from Chinese schools, we test the key ingredients of Situational Action Theory within the context of school bullying in a non-Western culture. The results show that morality has a robust effect on bullying behaviors, whereas control mechanisms (i.e., self-control and deterrence) have little restraining effect when personal morality is low. Our findings, together with prior mixed findings regarding conditional effects of control mechanisms, suggest that the moral filter may work differently for behaviors associated with different levels of stigmatization. We speculate that, for less stigmatized behaviors, “habitualization” easily materialize but “moral exclusion” does not, and thus controls exert stronger impact when morality is higher. Implications for the theory and directions for future research are discussed.